Disaster-related prenatal maternal stress predicts HPA reactivity and psychopathology in adolescent offspring: Project Ice Storm. (July 2020) - Yong Ping, Erin; Laplante, David P.; Elgbeili, Guillaume; Jones, Sherri Lee; Brunet, Alain; King, Suzanne
Highlights: The present study examined whether dysregulation of offspring HPA axis mediates the relationship between prenatal stress exposure and adolescent psychopathology. Maternal subjective distress and objective hardship was assessed in women who were pregnant during the Quebec ice storm of 1998. Greater maternal objective hardship was associated with elevated offspring cortisol reactivity in response to the Trier Social Stress Test at 13 years of age. Greater maternal subjective distress was associated with greater externalizing behaviors in offspring at 13 years of age. Cortisol reactivity in offspring did not mediate the association between maternal objective hardship or subjective distress and offspring externalizing or internalizing behaviors but was negatively associated with externalizing behaviors. Abstract: Background: Prenatal stress has been associated with adverse outcomes in offspring, including elevated risk of psychopathology. Fetal programming of the hypothalamic-pituitary-adrenal (HPA) axis has been posited as a biological mechanism underlying such consequences. The present study aimed to examine whether dysregulation of the offspring HPA axis mediates the relationship between prenatal stress exposure and adolescent psychopathology. Methods: Five months after the Quebec ice storm of 1998, women who had been pregnant at the time of the storm completed questionnaires about their objective hardship and subjective distress from the disaster. A total of 45 of their children, exposed to the ice storm in utero, participated at 13 years of age. Adolescents completed the Trier Social Stress Test while providing salivary samples to measure circulating cortisol levels. Maternal report of adolescent behaviors was assessed with the Child Behavior Checklist. Results: Results from the study found that greater objective hardship was associated with elevated offspring cortisol reactivity at 13 years of age. Furthermore, greater subjective distress was associated with greater externalizing behaviors. While lower cortisol reactivity predicted greater externalizing behaviors, it did not mediate the association between maternal objective hardship or subjective distress and offspring externalizing or internalizing behaviors. Conclusions: Findings suggest that objective hardship in pregnancy has long-term implications for offspring HPA axis functioning, which is also associated with externalizing behaviors. While dysregulation of the offspring HPA axis did not mediate the association between prenatal stress and offspring psychopathological symptoms, further research is warranted to investigate programming of alternative biological systems.